2019
DOI: 10.1021/acsearthspacechem.9b00197
|View full text |Cite
|
Sign up to set email alerts
|

Saccharide Transfer to Sea Spray Aerosol Enhanced by Surface Activity, Calcium, and Protein Interactions

Abstract: Sea spray aerosol (SSA) represents the largest source of natural primary aerosol with climate relevance in cloud formation. The aerosol-cloud activation process is influenced by saccharides, which comprise a large SSA organic mass fraction. Saccharides are enriched relative to sodium in SSA by several orders of magnitude but the mechanisms of that enrichment remain poorly understood. Here, saccharide enrichment in laboratory-generated SSA was quantified via bubble bursting experiments using marine-relevant mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 103 publications
7
56
0
Order By: Relevance
“…Enhanced saccharide enrichment in laboratory-generated SSA in the presence of divalent cations and other surface-active organic material strongly suggests a co-adsorption mechanism mediated by divalent cationic bridging. 12,31 A divalent cation mediated co-adsorption mechanism was also postulated by Schill et al to explain enrichment of the monosaccharide glucuronic acid in laboratory-generated SSA. 12 Glucuronic acid likely co-adsorbs to an insoluble palmitic acid (hexadecanoic acid, CH3(CH2)14COOH) monolayer via seawater divalent cationic bridging interactions.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Enhanced saccharide enrichment in laboratory-generated SSA in the presence of divalent cations and other surface-active organic material strongly suggests a co-adsorption mechanism mediated by divalent cationic bridging. 12,31 A divalent cation mediated co-adsorption mechanism was also postulated by Schill et al to explain enrichment of the monosaccharide glucuronic acid in laboratory-generated SSA. 12 Glucuronic acid likely co-adsorbs to an insoluble palmitic acid (hexadecanoic acid, CH3(CH2)14COOH) monolayer via seawater divalent cationic bridging interactions.…”
Section: Introductionmentioning
confidence: 86%
“…Hasenecz et al has shown that the polysaccharide alginate is enriched in laboratory-generated marine aerosol, and alginate enrichment can be enhanced upon adding protein and additional CaCl2 salt to the model seawater solution. 31 Alginate is a type of exopolymeric substance derived from marine brown algae and bacteria; 32,33 it is composed of (1→4)-linked α-ʟ-guluronic (G) and β-ᴅ-mannuronic (M) monomers that form a block copolymer with random sequences of M-, G-, and MG-blocks. [34][35][36][37][38][39] Alginate polymers undergo ionic crosslinking to form hydrophilic gels via metal ion coordination primarily to the G residue carboxylic acid moieties.…”
Section: Introductionmentioning
confidence: 99%
“…20,56 In tank and microcosm experiments, CCHO enrichments in aerosol particles increased after the addition of typical seawater matrix compounds, such as calcium, proteins, and heterotrophic bacteria, while short-chained DFCHO were not enriched. 57,58 However, once entered the atmosphere, OM undergoes complex changes; first, abiotically due to chemical reactions, e.g., with OH and NO 3 radicals, and also biologically by microbial degradation. 59,60 Latest studies revealed that airborne bacteria can survive in the atmosphere even in the harsh polar environments and are, similar to bacteria in seawater, metabolically active in the aqueous phase of clouds, as well as on the surface or in the bulk of aerosol particles.…”
Section: Introductionmentioning
confidence: 99%
“…Second, atmospheric aerosols can exhibit size-dependent properties. For example, Hasenecz et al observed an increase in the organic mass fraction with a decreasing particle size, reaching ∼70% for sub-180 nm SSAs . Furthermore, the morphologies of SSAs have been found to vary significantly with the particle size. Finally, atmospheric aerosols from the same source and similar size range can exhibit significant particle-to-particle variability .…”
Section: Introductionmentioning
confidence: 99%